From Texting to Tweeting: The Transformation of Written Language in the Digital Era - Muti'ah, Eva; Basrowi; Khaeruman (Center of Language and Cultural Studies, 2024)
The development of digital technology has brought significant changes in the way humans communicate, especially in written form. This article discusses the transformation of written language from short messages (texting) to the use of social media such as Twitter, which demands a more concise, creative and interactive communication style. Using a sociolinguistic approach, this research explores how technical constraints, such as the number of characters in a post, as well as social dynamics in the digital world, influence the structure and use of language. Research findings show that social media encourages the development of new forms of written language, such as abbreviations, acronyms, the use of emoji’s, and code-switching between languages. Apart from that, the phenomenon of viral in social media also contributes to the spread and normalization of new terms in various linguistic communities. In a broader context, these changes not only impact individual communication patterns but also influence language standards in educational, journalistic and professional domains. The implications of this transformation include the need for a deeper understanding of language adaptation in the digital realm and its impact on people's literacy competencies. Apart from that, this research also highlights the importance of linguistic policies that can balance digital language innovation and preserving standard language rules. Thus, this study provides insight into how the digital era has changed the way humans communicate in writing and how these changes continue to evolve as technology advances.